Integral Sliding Mode Control-Based Robust Bidirectional Platoon Control of Vehicles With the Unknown Acceleration and Mismatched Disturbance - Boo, Junseok; Chwa, Dongkyoung (IEEE Transactions on Intelligent Transportation Systems, 2023)
This paper proposes integral sliding mode control (ISMC)-based robust bidirectional platoon control methods in the longitudinal platoon for vehicles with unknown acceleration and mismatched disturbance. A finite time robust estimator (FTRE) is presented to estimate the practically unknown acceleration and mismatched disturbance of adjacent vehicles. In addition, the matched disturbance in the vehicle is also compensated for to further ensure the robustness of the platoon control. A modified constant time headway (MCTH) policy that removes the influence of the initial spacing and velocity error is defined to improve the transient response of the platoon control. Two robust platoon control methods, a nonlinear disturbance observer (DOB)-based ISMC and an adaptive dual-layer super-twisting ISMC (STISMC), are proposed. The proposed methods based on the nonlinear DOB and ISMC are more effective against highly nonlinear disturbances than the existing linear DOB-based methods and the disturbances can be compensated at all times by eliminating the reaching mode, unlike the exiting SMC-based methods. Furthermore, the proposed adaptive dual-layer STISMC provides a continuous control input that guarantees the finite time convergence of the sliding mode variables to zero without requiring an upper bound on disturbance. Both simulation and experimental results are provided to demonstrate the superior platoon control performance of the adaptive dual-layer STISMC method compared to both the existing linear DOB-based robust platoon control method using ISMC and the nonlinear DOB-based ISMC method.
Keywords: Constant time; Finite time robust estimator; Finite-time; Integral sliding mode control; Mismatched disturbance; Modified constant time headway policy; Platoon controls; Robust bidirectional platoon control; Robust estimators; Robustness; Sliding-mode control; Stability criterions; Time headway; Uncertainty; Unknown acceleration; Vehicle's dynamics; Finite time robust estimator (FTRE); integral sliding mode control (ISMC); mismatched disturbance; modified constant time headway (MCTH) policy; robust bidirectional platoon control; unknown acceleration